2020
DOI: 10.5713/ajas.19.0203
|View full text |Cite
|
Sign up to set email alerts
|

Quality comparison of retorted Samgyetang made from white semi-broilers, commercial broilers, Korean native chickens, and old laying hens

Abstract: The aim of this study was to compare the quality characteristics of retorted Samgyetang (Korean ginseng chicken soup) made from white semi-broilers (WSB; Ross× Hyline white, 3 weeks old), commercial broilers (CB; Ross, 4 weeks old), Korean native chickens (KNC; Hanhyup-3-ho, 12 weeks old) and old laying hens (OLH; Hyline white, 72 weeks old) and to explore the possibility of using the carcasses of KNCs and OLHs as raw material for product diversification. Methods: Raw and cooked meat quality, fatty acid compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 24 publications
5
25
0
1
Order By: Relevance
“…These results were in line with the study by Triyannanto et al (2014) , who did not find any difference after applying additional ingredients to samgyetang. The moisture content in this study was still within the range of previously reported studies ( Jeong et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…These results were in line with the study by Triyannanto et al (2014) , who did not find any difference after applying additional ingredients to samgyetang. The moisture content in this study was still within the range of previously reported studies ( Jeong et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…The protein percentage for breast meat ranged from 28.1%–28.9%, while it ranged from 24.1%–25.6% for thigh meat. This value was higher than that found in a previous study by Ali et al (2007) and still within the range reported in a study by Jeong et al (2020) . However, no effect was observed (p>0.05) by C. militaris mushrooms in this study, which might be due to the small addition percentage.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Samgyetang and Baeksuk are traditional Korean soups that are prepared using whole juvenile chickens filled with garlic, glutinous rice, jujube, and ginseng to combat the detrimental effects of the summer heat ( Jayasena et al, 2013 ). Considering its short and concentrated seasonal demand, Samgye is generally prepared and distributed using meat from white semi-broiler (WSB) chickens, which are crossbred using a male broiler and female laying hen ( Jeong et al., 2020 ). WSB is characterized by their white feathers, smaller size, and reduced fat and account for 60% to 70% of the Samgyetang market ( Cho et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%